Effect of sowing dates on the vegetative growth and yield parameters of two quinoa (Chenopodium quinoa Willd.) genotypes - Smail Mehda; Mabrouka Oustani; Sana Bouazza; Imane Djaballah (Future Science, 2023)
The aim of the present study was to select the best sowing time for two quinoa genotypes (Chenopodium quinoa Willd) grown in Ouargla, located in the Saharan region of Algeria. The adopted experimental device is of the random block type, comparing the effect of three sowing dates in 2018: October 16th, October 31st, and November 15th, on some vegetative growth parameters (number of seedlings raised, total number of plants, total fresh weight of plants, height of plants at panicle stage, number of branches per plant, average weight per plant), and yield parameters (number of panicles per plant, weight of the main panicle, weight of 1000 grains, and total weight of grains per square meter) of two quinoa genotypes: